A Critique of the Book: Natural Language Processing and Information Retrieval - Mortaza Kokabi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book entitled “Natural Language Processing and Information Retrieval” is a compiled and translated book, without any specific author, that has been translated by Jaafar Mehrad and Maryam Naseri. If we assume that information retrieval is the heart of the field of knowledge and information science, then we can claim that if it is done in user’s natural language, the language by which she/he lives and seeks information, the result will be much more useful for her/him. Therefore, a book on Natural Language Processing and Information Retrieval will be of great value for the information field and profession. Furthermore, the introduction of a course entitled “Natural Language Processing” in PhD curriculum with a minor of “Information Retrieval” necessitates the existence of such a book due to the shortage (and perhaps lack of) such a source for this course. However, there are some problems with the book that will be discussed in some detail in the section on the critique and evaluation of book’s content. Some other discussions will also be presented on the citation and referencing problems in the same section. Using some tables, the relationship among the terms translated in the book, vocabulary, and index will also be discussed.